Chemiluminescence Study of High Power Microwave Pulses Effects on Whole Blood - Abdulkader, Q. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Chemiluminescenc (CL), light emitted during chemical reaction, is one of the accurate methods used to detect directly oxygen free radicals. In this study, luminol was used as CL detector, to detect the concentration of free radicals formed in whole blood exposed to high power microwave pulses. The changes in the intensity of CL signal gives a clear relation between the concentration of free radicals formed by radiation in blood and changes in blood properties such as hemolysis of blood cells. This is done by measuring the electrical sytoplsimic electrical properties, the results are substituted in Maxwell-Wagner equation, to obtain electrical conductivity of cytoplasm, which is 18.3   ms/cm, while at suspension medium was 56.1 ms/cm, with specific absorption rate 1Kw/ gm and the total deposited energy per gm per pulse of 50 mJ.The over all temperature rise per pulse in suspension, red and white blood cells are, 0.017 0C, 0.004 oC and 0.003oC respectively. All these changes lead to increase the peak of CL signal compared with unexposed blood. This also indicates that, the formation of different reactive oxygen species in blood would increase and leads to the formation of hydrogen peroxide, which causes to enhance phagocytes behavior of leukocytes at the early time of exposure, but then causes blood hemolysis for later duration and causes membrane perturbation.